2000
DOI: 10.1021/bc990135y
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-Modification of the Phospholipid Vesicles by Using the Spontaneous Incorporation of Poly(ethylene glycol)-Lipid into the Vesicles

Abstract: The critical micelle concentrations of 1, 2-dipalmitoyl-sn-glycero-3-phosphoethanolamine-N-[monomethoxy poly(ethylene glycol) (5000)] (PEG-DPPE) and its distearoyl analogue (PEG-DSPE) were 70 and 9 microM, respectively, in buffer solutions ([Tris] = 20 mM, [NaCl] = 140 mM, pH 7.4) at 37 degrees C. When these PEG-lipid micelle dispersions were mixed with the dispersions of phospholipid vesicles comprised of a C16 membrane, of which the carbon number is 16, or a C18 membrane, the PEG-lipid micelles were dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 24 publications
8
128
0
2
Order By: Relevance
“…This saturation might be due to fixed quantity of α V β 3 integrin present on HUVEC cells. In addition, it was previously reported that the PEGylation ratio in liposomes was, at most, 5.0 mol% [35]. Collectively, 5.0 mol% of RGD-PEG might be the optimized modification condition in both aspects of cells and siRNA carriers.…”
Section: Discussionmentioning
confidence: 95%
“…This saturation might be due to fixed quantity of α V β 3 integrin present on HUVEC cells. In addition, it was previously reported that the PEGylation ratio in liposomes was, at most, 5.0 mol% [35]. Collectively, 5.0 mol% of RGD-PEG might be the optimized modification condition in both aspects of cells and siRNA carriers.…”
Section: Discussionmentioning
confidence: 95%
“…At time t, the fluorescent intensity was I t . The fraction of polymers that remained as micelles at time t after dilution can be expressed as [36]:…”
Section: Dissociation Kinetics Of the Mixed Micelles Upon Dilution Tomentioning
confidence: 99%
“…The stabilized TATplipoplexes could be targeted to the myocardium by the disease-specific mAb (to ischemic myocardium with the anti-myosin mAb 2G4). The incorporation of PEG-PE and the attachment of 2G4 antibody to TATp-lipoplexes were accomplished simultaneously by the so-called 'micelle transfer' procedure, 26,27 which provides simultaneous transfer of antibody-coupled micelles to liposome with negligible leakage. Thus, it is unlikely that the antibody coating affect DNA loading.…”
Section: Gene Therapy Using 2g4/tatp Double-targeted Lipoplexes Yt Komentioning
confidence: 99%
“…The anti-myosin antibody 2G4 was first conjugated to the micelle of pNP-PEG3400-PE and then inserted into the preformed TATp-lipoplexes by the 'micelle transfer' procedure. 26,27 Briefly, an amount of pNP-PEG3400-PE corresponding to 3 mol% of total lipids was hydrated in sodium citrate-buffered saline (5 mM, pH 5.0) and mixed with mAb 2G4 in sodium borate buffer (50 mM, pH 9.0) at a molar ratio of 40:1, corresponding to 169 mg antibody/mmol phospholipids. The mixture was incubated overnight and then dialyzed against 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid-buffered saline (10 mM, pH 7.4) with a cellulose ester membrane of MWCO 250 000 Da (Spectrum Medical Industries, Los Angeles, CA, USA) at 4 1C.…”
Section: Preparation Of 2g4-modified Tatp-lipoplexesmentioning
confidence: 99%